Indywidualne teorie na temat nauczania na odległość - Przemysław Wolski, Przemysław Wolski (Neofilolog, 2010)
The purpose of this article is to present similarities and differences between scientific and individual (subjective) theories on e-learning. Individual theories of students and teachers contain beliefs about pedagogical approaches, effectiveness and solutions of different didactic issues. The similarities can result both from knowledge of scientific literature and from professional experience.